2008
DOI: 10.1096/fj.08-119537
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal histidine triad proteins are regulated by the Zn 2+ ‐dependent repressor AdcR and inhibit complement deposition through the recruitment of complement factor H

Abstract: The pneumococcal histidine triad (Pht) proteins are a recently recognized family of surface proteins, comprising 4 members: PhtA, PhtB, PhtD, and PhtE. They are being promoted for inclusion in a multicomponent pneumococcal protein vaccine currently under development, but to date, their biological functions and their relative contributions to pathogenesis have not been clarified. In this study, the involvement of these proteins in pneumococcal virulence was investigated in murine models of sepsis and pneumonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
146
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 45 publications
(64 reference statements)
8
146
4
Order By: Relevance
“…Upon direct or indirect zinc starvation conditions, and hence a reduced intracellular concentration of this metal, repression by AdcR is relieved (Brenot et al, 2007;Claverys, 2001). However, and in contrast to what we have observed here, it was recently shown that the addition of zinc in culture medium elicits Pht production (Ogunniyi et al, 2009). Therefore, it is reasonable to estimate that production of Pht follows a bell-shaped curve within a given range of zinc concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Upon direct or indirect zinc starvation conditions, and hence a reduced intracellular concentration of this metal, repression by AdcR is relieved (Brenot et al, 2007;Claverys, 2001). However, and in contrast to what we have observed here, it was recently shown that the addition of zinc in culture medium elicits Pht production (Ogunniyi et al, 2009). Therefore, it is reasonable to estimate that production of Pht follows a bell-shaped curve within a given range of zinc concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…The results we have obtained from immunoblotting with protein extracts from the various Pht-deficient mutants tend to show that there is no compensation for gene loss by increasing the level of expression of the remaining pht gene products. This feature was also described recently at the RNA level by using RT-PCR (Ogunniyi et al, 2009).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding suggests that binding of anti-peptide antibodies to this exact region may block the Pht protein-zinc interaction and, therefore, hamper Pht proteins function, including zinc concentration homeostasis in the bacterial environment, adherence to epithelial cells, and C3b deposition inhibition, leading to impaired opsonophagocytosis and, therefore, attenuated bacterial virulence (14 -16, 24). In this regard, previous studies have shown that a quadruple S. pneumoniae mutant in which all Pht genes are deleted is completely avirulent (25), whereas antibodies against PhtD and PhtE prevent bacterial adhesion to the human respiratory epithelium (24). We are currently undertaking further studies to investigate how antibody binding may affect the zinc binding potential of zinc-finger B cell epitopes as well as their changes in conformation and function, as we have described previously in a different clinical setting (26).…”
Section: Discussionmentioning
confidence: 73%
“…Binding of complement inhibitor C4b-binding protein is restricted to certain serotypes, which possess a particular PspC allele (9). Pneumococcal histidine triad proteins may also play a role in complement evasion (35), but the impact they have on complement deposition seems to depend on the genetic background (29).…”
mentioning
confidence: 99%